Key audit matters: analyze of audit reports of financial institutions listed in B3 (Revista Brasileira de Contabilidade e Gestão, 2022)
Problems related to accounting audit failures have occurred in several countries since Enron and WorldCom took place. In this sense, the purpose of this study was to analyze the Key Audit Matters (KAM) in the audit reports referring financial statements of financial institutions, listed in Brazil Bolsa Balcão S/A (B3), for the years 2016, 2017 and 2018. The methodology is linked qualitative and quantitative, descriptive and documentary research. The statistics analytics was realized through mean, standard deviation, coefficient of variation and Kruskal-Wallis test. The results reveal that information technology environment, provisions for legal proceedings (tax claims, civil claims and labor claims) and allowances for doubtful accounts are KAM more disclosed by auditors in financial institution’s reports. The findings contribute to the understanding of the types of KAM, defined by independent auditors, when they examine the financial statements of financial institutions.
Keywords: main audit matters; independent audit; financial institution; audit; audit reports; B3; accounting statements